2020
DOI: 10.17979/ejge.2020.9.2.5850
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the perceived social impacts of the Formula E Grand Prix of Santiago de Chile

Abstract: The aim of this study is to analyse residents' perception of the social impact of the Formula E Grand Prix of Santiago de Chile. A sample of 414 residents was collected through a questionnaire made up of 46 items regarding possible positive and negative impacts. Descriptive analysis, confirmatory factorial analysis and cluster analysis were performed. The results showed two groups with different perceptions of this sporting event: realistic (n=152) and favourable (n=162). Sociodemographic variables referring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
1
7
1
Order By: Relevance
“…Additionally, hypothesis 3d cannot be accepted as fandom only had a positive significant direct influence on support after the event. Contrary to past research [3,13,15], participation in cycling and event attendance showed no significant direct influence on support before, during, or after the event. Consequently, hypotheses 3e and 3f cannot be accepted.…”
Section: Factors Influencing Supportcontrasting
confidence: 99%
See 3 more Smart Citations
“…Additionally, hypothesis 3d cannot be accepted as fandom only had a positive significant direct influence on support after the event. Contrary to past research [3,13,15], participation in cycling and event attendance showed no significant direct influence on support before, during, or after the event. Consequently, hypotheses 3e and 3f cannot be accepted.…”
Section: Factors Influencing Supportcontrasting
confidence: 99%
“…Therefore, hypothesis 3c can only party be accepted. Parra-Camacho et al [15] also evidenced this relationship, as they observed a relationship between attitudinal involvement (in terms of interest in the event) and support for the Formula E Grand Prix of Santiago de Chile in 2018 (which can be categorised as a non-mega SSE) after the event. Additionally, hypothesis 3d cannot be accepted as fandom only had a positive significant direct influence on support after the event.…”
Section: Factors Influencing Supportmentioning
confidence: 89%
See 2 more Smart Citations
“…There is a rising interest in social impact research in identifying the elements that assist to explain the correlations between the positive and negative impacts felt by the host community and support for staging sporting events. In this regard, some papers have tested the relationship of these variables with constructs such as satisfaction with the quality of life of residents [ [4] , [5] , [6] ], attitude towards events [ 7 ], perception of fair social distribution of event benefits and costs [ 8 ], trust in organizers [ 9 ] and in government [ 10 ].…”
Section: Introductionmentioning
confidence: 99%